Travelling in Brussels and feeling unsafe: women’s perceptions and strategies - Marie Gilow (Brussels Studies)
Equality between men and women in terms of travelling in the city is far from being a reality. One aspect of this imbalance is linked to feeling unsafe, which affects women in particular. This article analyses the diversity as well as the scope of the feeling of being unsafe as experienced by women, in their ways of travelling in the city. This problem calls for a reflection on the interiorisation of the social differentiation between the sexes and the way in which it affects the relationship with one’s surroundings, in particular in a context of anonymity specific to an urban environment. The study presented in this article has an exploratory character, and is based on semi-structured interviews conducted with ten women who live in Brussels.